Identification of new susceptibility loci for gastric non-cardia adenocarcinoma: pooled results from two Chinese genome-wide association studies. Issue 4 (23rd December 2015) - Wang, Zhaoming; Dai, Juncheng; Hu, Nan; Miao, Xiaoping; Abnet, Christian C; Yang, Ming; Freedman, Neal D; Chen, Jinfei; Burdette, Laurie; Zhu, Xun; Chung, Charles C; Ren, Chuanli; et al.
Abstract : Objective: Although several genome-wide association studies (GWAS) of non-cardia gastric cancer have been published, more novel association signals could be exploited by combining individual studies together, which will further elucidate the genetic susceptibility of non-cardia gastric cancer. Design: We conducted a meta-analysis of two published Chinese GWAS studies (2031 non-cardia gastric cancer cases and 4970 cancer-free controls) and followed by genotyping of additional 3564 cases and 4637 controls in two stages. Results: The overall meta-analysis revealed two new association signals. The first was a novel locus at 5q14.3 and marked by rs7712641 (per-allele OR=0.84, 95% CI 0.80 to 0.88; p=1.21×10 −11 ). This single-nucleotide polymorphism (SNP) marker maps to the intron of the long non-coding RNA, lnc-POLR3G-4 ( XLOC_004464 ), which we observed has lower expression in non-cardia gastric tumour compared with matched normal tissue (Pwilcoxon signed-rank =7.20×10 −4 ). We also identified a new signal at the 1q22 locus, rs80142782 (per-allele OR=0.62; 95% CI 0.56 to 0.69; p=1.71×10 −19 ), which was independent of the previously reported SNP at the same locus, rs4072037 (per-allele OR=0.74; 95% CI 0.69 to 0.79; p=6.28×10 −17 ). Analysis of the new SNP conditioned on the known SNP showed that the new SNP remained genome-wide significant (Pconditional =3.47×10 −8 ). Interestingly, rs80142782 has a minor allele frequency of 0.05 in East Asians but is monomorphic in both European and African populations. Conclusion: These findings add new evidence for inherited genetic susceptibility to non-cardia gastric cancer and provide further clues to its aetiology in the Han Chinese population.